What's new with APOS theory? A look into levels and Totality - Asuman Oktac (Sociedad Española de Investigación en Educación Matemática, 2022)
This paper focusses on developments concerning transitional aspects of learning from the perspective of APOS (Action-Process-Object-Schema) theory. Recent investigations about levels between stages and Totality as a possible new structure are commented on, as well as offering related pedagogical suggestions and ideas for future research.